Comparative transcriptome analysis of clinical and environmental strains of cryptococcus neoformans and an investigation on anti-cryptococcus activity of triclosan / Elaheh Movahed - Elaheh, Movahed (2017)
Cryptococcus neoformans is an opportunistic yeast pathogen which causes meningoencephalitis particularly in HIV-infected patients. The infection can be acquired through the inhalation of desiccated yeast cells and basidiospores originated from the environment, especially from soil contaminated with bird droppings. C. neoformans environmental strains display differences in the virulence patterns. Several cellular factors that have been associated with the virulence of C. neoformans, include melanin, components of polysaccharide capsule, alpha mating type and phospholipase. At present, the mechanism of gene control in clinical and environmental strains of C. neoformans that leads to the virulence of C. neoformans is not well understood. This study aims to determine if gene expression differences among clinical and environmental C. neoformans strains contributes to different degree of virulence. Additionally, due to the emergence of drug-resistant C. neoformans in recent years, this study also aims to investigate the anti-Cryptococcus activity of triclosan (2,4,4'-trichloro-2'-hydroxydiphenylether, C12H17Cl3O2). A clinical strain (H99) and three environmental strains (H4, S48B and S68B) isolated from soil contaminated with bird droppings were included in this investigation. All the cryptococcal strains were first characterized for their virulence properties using in vitro and in vivo approaches. India ink staining showed a bigger capsule size in C. neoformans H99 strain compared to environmental strains. In the in vivo challenge model, an average of 4.73 ± 1.19 × 105 colony forming units (cfu)/ml of C. neoformans were obtained from the lung homogenates of mice infected intranasally with strain H99. The recovered yeast cells were approximately forty folds higher than those obtained from H4-, S48B-, and S68B-infected mice. To understand the gene transcription underlying the differences in virulence among H99 and environmental strains, RNA was extracted from each strain and a genome-wide microarray study was performed. Microarray analysis revealed a iv different transcriptome profile of H99 strain compared to H4, S48B and S68B strains. Out of 7,419 genes (22,257 probes) examined, 41 genes were up-regulated while 24 genes were down-regulated in H99 versus environmental strains. The genes which were up-regulated in H99 strain include Hydroxymethylglutaryl-CoA synthase (MVA1), Mitochondrial matrix factor 1 (MMF1), Bud-site-selection protein 8 (BUD8), High affinity glucose transporter 3 (SNF3) and Rho GTPase-activating protein 2 (RGA2). Pathway annotation using DAVID bioinformatics resource showed that metal ion binding pathway was highly active in the H99 but not in the environmental strains. Transition metals such as iron, zinc, copper, and manganese are essential elements for the growth and survival of microorganisms including fungi. Siderophore iron transporter genes (ARN1 andARN2) were up-regulated at 6.7-, 10.2-, and 11.4-folds, and 4.7-, 8.1-, and 5.5-folds, respectively, in H99 strain compared to H4, S48B and S68B strains. Sugar transmembrane transport, another active pathway identified in H99 strain, is essential for the production of capsular polysaccharide antigens in C. neoformans. One of the genes in the pathway, SNF3, was up-regulated at 15.2-, 8.0- and 5.5-folds in H99 versus H4, S48B and S68B strains. The analyses in this study suggest possible roles of the relevant genes and pathways in fungal pathogenesis. In the second part of the study, growth inhibition against C. neoformans by triclosan was demonstrated. A combination of triclosan with amphotericin B or with fluconazole enhanced the fungicidal effects against C. neoformans. Triclosan-treated C. neoformans displayed characteristics such as nuclear chromatin condensation, extensive intracellular vacuolation and mitochondrial swelling, which were suggestive of apoptosis-like cell death. In conclusion, this study has linked several genes and pathways in C. neoformans with the higher virulence of the H99 strain, as compared to the environmental strains. This study also reports a potential therapeutic value of triclosan as a novel drug or a synergent in the treatment of cryptococcal infection.